2007
DOI: 10.1509/jmkg.71.2.079
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Performance Measurement Ability and Firm Performance

Abstract: Marketing practitioners are under increasing pressure to demonstrate their contribution to firm performance. It has been widely argued that an inability to account for marketing's contribution has undermined its standing within the firm. To respond to this pressure, marketers are investing in the development of performance measurement abilities, but to date, there have been no empirical studies of whether the ability to measure marketing performance has any actual effect on either firm performance or marketing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
2
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(157 citation statements)
references
References 63 publications
3
143
2
9
Order By: Relevance
“…Past studies have demonstrated that knowledgeable senior managers can provide information as reliable and as valid as that obtained from multiple firm respondents (e.g., Atuahene-Gima & Murray, 2004). The senior marketing manager was identified by referring to the top member of the marketing team by title as listed in the database (O'Sullivan & Abela, 2007). The continued employment of each senior marketing manager was randomly confirmed through corporate web site inspections or phone calls to the company.…”
Section: Data Collectionmentioning
confidence: 99%
“…Past studies have demonstrated that knowledgeable senior managers can provide information as reliable and as valid as that obtained from multiple firm respondents (e.g., Atuahene-Gima & Murray, 2004). The senior marketing manager was identified by referring to the top member of the marketing team by title as listed in the database (O'Sullivan & Abela, 2007). The continued employment of each senior marketing manager was randomly confirmed through corporate web site inspections or phone calls to the company.…”
Section: Data Collectionmentioning
confidence: 99%
“…Assessing loyalty programs is simply one specific instance in the measurement of marketing activities. By ''activities'', researchers mean the tactics of operational marketing rather than the underlying strategies (Rust et al, 2004;O'Sullivan and Abela, 2007). Because loyalty programs are levers of operational marketing, measuring their performance becomes a key issue.…”
Section: The Effectiveness Of Loyalty Programs As Results and Processmentioning
confidence: 99%
“…Such a definition assesses accountability as a capability of a firm, in line with our proposed framework; however, it does not demonstrate enough of the substance of the marketing accountability concept and how it should be constructed. Terms that usually appear hand in hand with marketing accountability include: marketing metrics (Clark, 1999), marketing productivity (Sheth & Sisodia, 2002) and marketing performance (O'Sullivan & Abela, 2007). Marketing productivity and performance should be the outcome of marketing accountability, while marketing metrics should represent one of its elements.…”
Section: Marketing Accountabilitymentioning
confidence: 99%
“…However, accounting and finances cannot compute these metrics without guidance from marketing. Bibliometric analysis reveals a broad research field that deals with marketing metrics and performance and productivity measures Moorman & Rust, 1999;O'Sullivan & Abela, 2007;Rust, Ambler, Carpenter, Kumar, & Sirvastava, 2004;Sheth & Sisodia, 2002). It is also important to note that the managerial accounting approach to marketing metrics brings potential dangers to metrics' effectiveness; the main dangers are in the unsystematic representation of the measures, inconsistent disclosures over time (Simpson, 2010) and the need for coordination between marketing and accounting activities (Sidhu & Roberts, 2008).…”
Section: Marketing Accountabilitymentioning
confidence: 99%